Tourism Planning for the Najaf Depressions (Lake Najaf): A Vision for Urban and Regional Planning - المسافر, طالب طارش طاهر (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study explores the planning and tourism potentials of the Najaf Depression، particularly Lake Najaf ، through an approach grounded in the concepts of sustainable urban and regional planning. Lake Najaf is considered a significant natural resource ، possessing substantial environmental and tourism potential. However ، it suffers from neglect ، poor planning، and a lack of integration into local development strategies. The research aims to analyze the geographical and natural characteristics of Lake Najaf ، assess the current tourism and urban realities ، and then present an integrated and feasible planning vision. The study adopts the descriptive - analytical method ، the case study approach ، and urban planning methodology to identify the strengths ، weaknesses ، opportunities ، and challenges of the Lake Najaf area. The findings indicate that Lake Najaf could be transformed into a sustainable and integrated environmental and tourism center if a phased plan is adopted. This plan should include infrastructure development ، enhancement of tourism services ، and linking the area with other attraction centers in the governorate and across Iraq within a comprehensive and executable regional vision. The study recommends that all local institutions and the private sector participate in the planning process. It also calls for the activation of legislation protecting natural resources and the development of tourism marketing plans that rely on the cultural and religious identity of Najaf. Moreover ، it advocates for the establishment of a local authority specialized in managing and planning Lake Najaf and its surrounding depressions to ensure the effective role of tourism in sustainable development.